Introgression of Maize Lethal Necrosis Resistance Quantitative Trait Loci Into Susceptible Maize Populations and Validation of the Resistance Under Field Conditions in Naivasha, Kenya - Awata, Luka A. O.; Ifie, Beatrice E.; Danquah, Eric; Jumbo, MacDonald Bright; Suresh, L. Mahabaleswara; Gowda, Manje; Marchelo-Dragga, Philip W.; Olsen, Michael Scott; Shorinola, Oluwaseyi; Yao, Nasser Kouadio; Boddupalli, Prasanna M.; Tongoona, Pangirayi B. (Frontiers in Plant Science, 2021)
Maize lethal necrosis (MLN), resulting from co-infection by maize chlorotic mottle virus (MCMV) and sugarcane mosaic virus (SCMV), can cause up to 100% yield losses in maize in Africa under serious disease conditions. Maize improvement through conventional backcross takes many generations but can significantly be shortened when molecular tools are utilized in the breeding process. We used a donor parent (KS23-6) to transfer QTL for resistance to MLN into nine adapted but MLN susceptible lines. Nurseries were established in Kiboko, Kenya during 2015-2017 seasons and BC3F2 progeny were developed. Six single nucleotide polymorphism (SNP) markers linked to quantitative trait loci (QTL) for resistance to MLN developed by International Maize and Wheat Improvement Center (CIMMYT) from separate populations were used to genotype 2400 BC3F2 lines using Kompetitive Allele Specific PCR (KASP) platform. The present study detected that two of the six QTL had major effects for resistance to MLN under artificial inoculation field conditions in 56 candidate BC3F2lines. To confirm whether these two QTL are reproducible under different field conditions, the 56 BC3F2 lines including their parents were evaluated in replicated trials for two seasons under artificial MLN inoculations in Naivasha, Kenya in 2018. Strong co-segregation of genotype with phenotype was detected. Consequently, 19 superior BC3F2 lines with favourable alleles and showing improved levels of resistance to MLN under artificial inoculation in the field were identified. We, therefore, believe that these elite lines could be superior genetic sources for improvement of maize hybrids for resistance to MLN. Furthermore, the validated two major QTL can be utilized to speed up the breeding process by selecting plants with favorable alleles for resistance to MLN in a marker assisted backcross breeding approach.